2014
DOI: 10.1007/s13592-014-0320-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations on possible pathogen spill-over from Apis mellifera to Apis cerana

Abstract: International audiencePopulations of Apis mellifera and Apis cerana in China and Vietnam were surveyed in order to study possible pathogen spill-over from European to Asian honeybees. This is the first survey of the prevalence of honeybee pathogens in apiaries in Vietnam, including pathogen prevalence in wild A. cerana colonies never in contact with A. mellifera. The bee samples were assayed for eight honeybee viruses: deformed wing virus (DWV); black queen cell virus (BQCV); sac brood virus (SBV); acute bee p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Currently, A. mellifera occurs throughout most of the natural distribution area of A. cerana in Asia (Yañez et al, 2015). This has led to interspecific pathogen transmission from A. mellifera to A. cerana (Forsgren et al, 2015;Lin et al, 2016) or vice versa some pathogens also can be spread from native A. cerana to A. mellifera (Rath, 1999;Paxton et al, 2007;Locke et al, 2012). However, little is known about P. larvae incidence in Asiatic cavity-nesting honey bees; Apis cerana (Chen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, A. mellifera occurs throughout most of the natural distribution area of A. cerana in Asia (Yañez et al, 2015). This has led to interspecific pathogen transmission from A. mellifera to A. cerana (Forsgren et al, 2015;Lin et al, 2016) or vice versa some pathogens also can be spread from native A. cerana to A. mellifera (Rath, 1999;Paxton et al, 2007;Locke et al, 2012). However, little is known about P. larvae incidence in Asiatic cavity-nesting honey bees; Apis cerana (Chen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Interspecific transmission of pathogens between different host systems is currently viewed as one of the most essential sources of biodiversity loss and honey bee colony losses in particular (Forsgren et al, 2015). Many studies have reported interspecific transmission of pathogens in different honey bees such as Nosema spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, seven are common including BQCV, DWV, KBV, SBV, ABPV, Chronic bee paralysis virus (CBPV), and Israeli acute paralysis virus (IAPV) (Chen and Siede 2007). In Asia, these seven viruses have been reported to infect different honeybee species throughout the region (Sanpa and Chantawannakul 2009;Ai et al 2012;Forsgren et al 2015 Iflaviridae, whereas BQCV, ABPV, KBV, and IAPV belong to the Dicistroviridae.…”
Section: Virusesmentioning
confidence: 99%
“…In A. cerana , it was observed in India, Thailand, South Korea, Japan, Nepal, China, and Vietnam (Shah and Shah 1988;Allen and Ball 1996;Choi et al 2008;Kojima et al 2011;Grabensteiner et al 2007;Ai et al 2012;Forsgren et al 2015). SBV infection of A. mellifera colonies was detected in Thailand, South Korea, Jap a n , C h i n a , a n d Vi e t n a m ( S a n p a a n d Yoo et al 2009;Kojima et al 2011;Ai et al 2012;Forsgren et al 2015).…”
Section: Iflaviridaementioning
confidence: 99%